2013
DOI: 10.1136/bmjopen-2013-002963
|View full text |Cite
|
Sign up to set email alerts
|

Trends in ischaemic heart disease hospitalisation and case fatality in the Hong Kong Chinese population 2000–2009: a secondary analysis

Abstract: ObjectivesThis study examines the recent trends in ischaemic heart disease (IHD) incidence and case fatality in Hong Kong and explores the possible risk factors.DesignRetrospective observational study.SettingAll public hospitals in Hong Kong.Outcome measuresIncidence rate was defined as the number of IHD inpatient episodes divided by the size of the corresponding population. Short-term and long-term case fatality rate was defined as deaths from all causes occurring within 30 and 31–365 days, respectively, divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…By contrast, stable, rather than decreasing, IHD hospitalisation trends have been reported in Hong Kong8 and British Columbia,9 and increasing IHD mortality rates in South and East Asia 3. The continued decline in IHD mortality in most high-income countries has been attributed to a combination of improved primary (improvements in risk factors) and secondary (improved treatment of acute and chronic IHD) prevention 26 27.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, stable, rather than decreasing, IHD hospitalisation trends have been reported in Hong Kong8 and British Columbia,9 and increasing IHD mortality rates in South and East Asia 3. The continued decline in IHD mortality in most high-income countries has been attributed to a combination of improved primary (improvements in risk factors) and secondary (improved treatment of acute and chronic IHD) prevention 26 27.…”
Section: Resultsmentioning
confidence: 99%
“…Population incidence has been reported for both acute and subacute forms of ischemic heart disease (ICD-9-CM diagnosis code 411 and all subcodes), angina pectoris (ICD-9-CM diagnosis code 413 and all subcodes), and other forms of chronic ischemic heart disease (ICD-9-CM diagnosis code 414 and all subcodes). 23 Employing the same classification method showed that 68 patients incurred 153 episodes of ischemic heart disease during subsequent admissions. Compared to the general population, epilepsy patients had elevated risk of developing ischemic heart disease (overall: SIR 4.18, 95% CI 3.54-4.91; female: SIR 6.25, 95% CI 4.89-7.87; male: SIR 3.21, 95% CI 2.54-4.00) (table e-5D).…”
Section: Resultsmentioning
confidence: 99%
“…Age-and sex-specific standardized incidence ratios (SIR) for stroke, ischemic heart disease and cancer in epilepsy patients without baseline comorbidities were compared with general population data that were also derived from HA's data repository. [21][22][23] Byar approximation 24 was used to calculate the 95% confidence interval (CI) for standardized ratios. A generalized linear model with log-binomial regression was used to estimate the relative risks (RRs) of developing new comorbidities in the defined AED monotherapy subgroups, adjusted for age and sex.…”
mentioning
confidence: 99%
“…From a public health and policy perspective, it can be seen that continuing research into prevention and management strategies will be important for both non-communicable diseases as well as geriatric syndromes, to ensure that it is not only life expectancy that is increased, but also the quality of life, by promoting independence and reducing reliance on elderly care services. Regular monitoring of trends in incidence and case fatalities of common chronic diseases would enable estimates of future disease burdens and guide preventive health policies ( Chau et al, 2013a , b ). In addition, solutions to trends in the occurrence of disability and frailty are also needed ( Yu et al, 2018b ).…”
Section: Responses To the Challenges Of Ageing In Chinamentioning
confidence: 99%